ANALISIS KURIKULUM MERDEKA DALAM PROSES PEMBELAJARAN OLEH GURU DI SMA NEGERI 1 MUARO JAMBI - Novita Dwijayanti; Siti Syuhada; Hidayatul Arief (Jurnal Manajemen Pendidikan, 2026)
This study employed a qualitative approach using a descriptive research design. The research was conducted at SMA Negeri 1 Muaro Jambi, with informants consisting of the principal, the vice principal for curriculum affairs, and teachers. Data were collected through in-depth inte rviews and documentation. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation. The findings indicate that the implementation of the Merdeka Curriculum in the teaching and learning process at SMA Negeri 1 Muaro Jambi has been carried out through four stages: learning and assessment planning, implementation of learning and assessment, processing and reporting of assessment results, and reflection and follow-up of learning activities. Supporting factors for the implementation of the Merdeka Curriculum include learning communities, In-House Training (IHT), teacher collaboration, and school support. Meanwhile, the inhibiting factors are changes in curriculum policies, varying levels of teacher readiness, and students’ lack of optimal focus. To ensure that the Merdeka Curriculum is implemented in accordance with established guidelines, the school conducts academic supervision, evaluates instructional materials and learning plans, provides teacher training and mentoring, and strengthens collaboration among teachers. Based on the results of the study, it can be concluded that the Merdeka Curriculum at SMA Negeri 1 Muaro Jambi has been implemented effectively and in accordance with government guidelines.